Wire electrical discharge machining characteristics of rare earth oxides reinforced AZ91D magnesium alloy hybrid composite using Taguchi-grey relational analysis approach - Santhosh Gotagunaki; Vardhaman S. Mudakappanavar; R. Suresh (Hybrid Advances, 2023)
The objective of the present study was to investigate the influence of machining parameters on performance for Wire Electrical Discharge Machining (WEDM) of Rare Earth (RE) oxides (Y2O3 and CeO2) particles reinforced AZ91D hybrid metal matrix composites. Taguchi's plan of experiments was implemented for the conduction of experimental trials. Pulse on, pulse off and peak current were considered as process parameters with each varied at 3 levels. Material removal rate, surface roughness and electrode wear were studied as responses. The ANOVA analysis revealed that, individual effect of parameters on responses was significant. In addition, pulse-on with pulse-off interaction effect on response was also remarkable. The main effect plots shown that, MRR and surface roughness and electrode wear studied were found to increase with the increase of pulse on and peak current and decreased with increase of pulse off. Further, regression models were developed to correlate the machining parameters with responses. The R-Sq. and R-Sq. (adj.) values of models were >85 %, which suggests that models are feasible to predict the responses within the studied range of parameters. The surface impurities like, recast layer, surface void, globule and craters were observed on the machined surface under higher cutting conditions.